Peer support on the "inside and outside": building lives and reducing recidivism for people with mental illness returning from jail. Issue 3 (7th August 2019) - Bellamy, Chyrell; Kimmel, James; Costa, Mark N.; Tsai, Jack; Nulton, Larry; Nulton, Elissa; Kimmel, Alexandra; Aguilar, Nathan J.; Clayton, Ashley; O'Connell, Maria
Abstract : Purpose: The purpose of this paper is to gain understanding about the effectiveness of a forensic peer support program's impact on reducing criminal recidivism. People with histories of mental illness returning to the community following incarceration face tremendous challenges in jails and prisons and in successful reentry to community. Transitioning from jails and prisons is fraught with additional challenges such as reconnecting or connecting with mental health and substance abuse treatment, finding adequate housing, finding employment, reuniting with family and friends, etc. Unfortunately, recidivism remains high, principally because of these challenges. Many state and local authorities have supported the development of the forensic peer specialist. Design/methodology/approach: Kaplan–Meier survival analyses were conducted to examine time to re-incarceration. Findings: The population served was determined to be a particularly high risk of re-incarceration population, when released from prison. All had a mental illness diagnosis, with 80 percent diagnosed with at least one serious mental illness, and more than 50 percent had three or more anterior incarcerations. Utilizing Kaplan–Meyer survival analysis, the chance of re-incarceration for participants after one year was of 21.7 percent. Surprisingly, in the first year after release from prison, participants did much better than those in the general US prison population when in terms of re-incarceration rates (21.7 percent vs 43.4 percent). Originality/value: While preliminary findings of this approach, this study reaffirms the idea that forensic peer support programs are beneficial in reducing recidivism rates for people diagnosed with a mental illness coming out of prison, offering individuals supports to maintain their lives in the community.